Improving Student’s Discipline Through Islamic Education Management - Fauzi, Fauzi; Pepilina, Dini; Warisno, Andi; Andari, An An; Anshori, M Afif (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2023)
At Islamic boarding schools, student’s discipline education is the most effective method of education. As a result, everyone involved in Islamic boarding schools, including students, teachers, and Islamic Boarding School caretakers, must uphold discipline education. The discipline is divided into several categories: manners, cleanliness, worship, language, boarding, dress, exercise, and language. Everything must be strictly followed from the moment students officially join the Islamic Boarding School. Baitul Qur'an Pringsewu Islamic Boarding School is one example of a boarding school that can incorporate discipline education into daily life. This study takes a descriptive research approach. This study lacks a hypothesis because it is not intended to test hypotheses that have been developed to be rejected or accepted, but rather to collect data to describe the actual situation in the field. It runs smoothly and effectively, based on the findings of Islamic education management research into improving student’s discipline at the Baitul Qur'an Pringsewu Islamic Boarding School.